Correction: Real-world application of a scalable school-based physical activity intervention: A cross-sectional survey of the implementation of The Daily Mile in Greater London primary schools. - Bina Ram; Esther van Sluijs; Anna Chalkley; Dougal Hargreaves; Sonia Saxena (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288500.].